Whole‐exome sequencing improves the diagnosis yield in sporadic infantile spasm syndrome. Issue 2 (30th July 2015) - Dimassi, S.; Labalme, A.; Ville, D.; Calender, A.; Mignot, C.; Boutry‐Kryza, N.; de Bellescize, J.; Rivier‐Ringenbach, C.; Bourel‐Ponchel, E.; Cheillan, D.; Simonet, T.; Maincent, K.; et al.
Abstract : Infantile spasms syndrome (ISs) is characterized by clinical spasms with ictal electrodecrement, usually occurring before the age of 1 year and frequently associated with cognitive impairment. Etiology is widely heterogeneous, the cause remaining elusive in 40% of patients. We searched for de novo mutations in 10 probands with ISs and their parents using whole‐exome sequencing (WES). Patients had neither consanguinity nor family history of epilepsy. Common causes of ISs were excluded by brain magnetic resonance imaging (MRI), metabolic screening, array‐comparative genomic hybridization (CGH) and testing for mutations in CDKL5, STXBP1, and for ARX duplications. We found a probably pathogenic mutation in four patients. Missense mutations in SCN2A (p.Leu1342Pro) and KCNQ2 (p.Ala306Thr) were found in two patients with no history of epilepsy before the onset of ISs. The p.Asn107Ser missense mutation of ALG13 had been previously reported in four females with ISs. The fourth mutation was an in‐frame deletion (p.Phe110del) in NR2F1, a gene whose mutations cause intellectual disability, epilepsy, and optic atrophy. In addition, we found a possibly pathogenic variant in KIF3C that encodes a kinesin expressed during neural development. Our results confirm that WES improves significantly the diagnosis yield in patients with sporadic ISs.